2017
DOI: 10.1186/s13046-017-0526-0
|View full text |Cite
|
Sign up to set email alerts
|

Itraconazole induces apoptosis and cell cycle arrest via inhibiting Hedgehog signaling in gastric cancer cells

Abstract: BackgroundItraconazole has been proved therapeutically effective against a variety of human cancers. This study assessed the effect of itraconazole on the Hedgehog (Hh) pathway and proliferation of human gastric cancer cells.MethodsCCK-8 assay and colony formation assay were used to assess the effects of itraconazole on proliferation of gastric cancer cells. The expression of Hh signaling components in gastric cancer cells treated with itraconazole was evaluated by reverse-transcription polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 41 publications
(49 reference statements)
3
39
0
Order By: Relevance
“…In the etiology of GC, it has been confirmed that GLI1 is involved in H. pylori infection and promotes chronic information ( 24 , 25 ). Furthermore, the mechanism through which GLI1 enhances GC development involves many oncogenes, such as NAPDH oxidase 4 ( 26 ), Mucin 5AC, Oligomeric Mucus/Gel-Forming ( 27 ), and Wnt proteins ( 28 ), leading to increased resistance to chemotherapy drugs ( 29 , 30 ). Recently, it was shown that Hh signaling via Smoothened and GLI1 requires involvement of the RAB family ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the etiology of GC, it has been confirmed that GLI1 is involved in H. pylori infection and promotes chronic information ( 24 , 25 ). Furthermore, the mechanism through which GLI1 enhances GC development involves many oncogenes, such as NAPDH oxidase 4 ( 26 ), Mucin 5AC, Oligomeric Mucus/Gel-Forming ( 27 ), and Wnt proteins ( 28 ), leading to increased resistance to chemotherapy drugs ( 29 , 30 ). Recently, it was shown that Hh signaling via Smoothened and GLI1 requires involvement of the RAB family ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…As changes in cell proliferation are usually accompanied by changes in the cell cycle ( 28 ), the present study next evaluated the effect of EMCL on the cell cycle. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, through flow cytometry and western blot analysis, Chen et al [ 23 ] observed that ketoconazole was able to induce growth arrest in G0/G1 phase in three cancer cells (COLO 205, Hep G2, and HT 29), which is probably due to decrease in cyclin D3 and CDK4 proteins. Itraconazole showed similar effects in gastric cancer cells [ 24 ]. Fluconazole-induced MN was also observed in newborn pups after transplacental exposure [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%